2014
DOI: 10.1123/rsj.2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Student Awareness of University Adventure Programs: Understanding Motivations and Constraints

Abstract: Participation rates among college students in adventure programs (AP) have been problematic in recent years. While AP managers focus on the quality of programs offered to students, little effort has addressed reducing constraints to participation, improving program offerings, and effectively marketing AP at colleges and universities. The purpose of this investigation was to identify the constraints and motivations to AP participation. A survey was administered to 193 college students. Overall, respondents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Existing studies (Watson et al, 2010;Amani, 2016;) have shown that feasible choice and decision-making depend on knowledge and information. According to Flood and Parker (2014) a lack of adequate awareness of students about a university's programme can demotivate them and constrain them from seeing the potential in the programme. Incomplete information could also reduce motivation, reduce academic performance and increase dropout when the unexpected begins to http://ijlter.org/index.php/ijlter show up during the programme.…”
Section: Information Asymmetry About Ecpmentioning
confidence: 99%
“…Existing studies (Watson et al, 2010;Amani, 2016;) have shown that feasible choice and decision-making depend on knowledge and information. According to Flood and Parker (2014) a lack of adequate awareness of students about a university's programme can demotivate them and constrain them from seeing the potential in the programme. Incomplete information could also reduce motivation, reduce academic performance and increase dropout when the unexpected begins to http://ijlter.org/index.php/ijlter show up during the programme.…”
Section: Information Asymmetry About Ecpmentioning
confidence: 99%
“…While many campus recreation studies have focused on the role of constraints to physical activity (e.g., Flood & Parker, 2014;Stankowski et al, 2017;Young et al, 2003) few have examined how constraints to physical activity and constraint negotiation strategies relate to general physical activity and SRSC usage. The purpose of this research was to determine the extent to which psychosocial factors related to physical activity constraints and negotiations to SRSC usage among college students.…”
Section: Research Questionsmentioning
confidence: 99%